Parental support for physical activity and children's physical activities: a cross-sectional study - Rikuya Hosokawa; Megumi Fujimoto; Toshiki Katsura (BMC, 2023)
Abstract Background Physical activity (PA) in school-aged children is imperative for physical and mental development. However, there has been reduced PA among children in recent years owing to environmental changes, resulting in declining physical strength and athletic ability. Although parents' and children's PA has been found to be correlated, the specific parental caregiving attitudes associated with children's actual levels of PA during school-age years remain unknown. Therefore, this study aimed to examine the relationship between parental support for PA and children's levels of PA. Methods In 2017, a self-reported questionnaire survey was administered to 1,515 third-grade students (8-9 years old) and their caregivers in Nagoya, Aichi, a major metropolitan area in Japan. The main items surveyed included the attitudes of children and parents towards PA and the children's actual PA level. Multiple regression analysis was conducted with parental involvement related to PA as the explanatory variable and children's PA as the objective variable. Results In total, 717 children with valid responses were included in the analysis. The mean age of the children was 9.08 ± 0.33 years; 366 (51.0%) were boys, and 351 (49.0%) were girls. For moderate-to-vigorous and vigorous PA, PA levels tended to be significantly higher in children whose parents provided logistic support such as enrolling their children in a sports club. However, for moderate PA and walking, PA levels tended to be significantly higher in children whose parents used community resources. Modeling and limiting sedentary activities were not associated with children's PA. Conclusions The results of this study suggest that direct parental assistance for PA such as logistic support encourages children to engage in moderate-to-vigorous PA; in addition, parental use of community resources may encourage children to engage in moderate and light PA such as walking. Conversely, indirect and negative involvement such as modeling and limiting sedentary activities were not associated with children's PA. Therefore, logistic support may need to be strengthened to encourage moderate-to-vigorous and vigorous PA, which is important for children's health.